Peran Alumni Pondok Pesantren Darussalam Kampung Banjir Dalam Pembinaan Keagamaan Masyarakat di Kelurahan Pasar Gunung Tua - Hamdan Akbar (AL-IBROH: Jurnal Ilmu Pendidikan dan Keguruan, 2024)
The concrete manifestation of alumni roles is to serve as mediators or exemplary examples in religious and social activities within the community. Ideally, an alumni of an Islamic educational institution who has completed their studies and obtained a degree should also be proficient in applying the knowledge they have acquired. Education is inseparable from the surrounding environment that influences it, especially with a community that has interdependent relationships. This research is a field study aimed at gaining an in-depth understanding of the role of alumni in nurturing religious practices within the community of Pasar Gunung Tua District. The results obtained indicate that: 1) The role of alumni from Darussalam Islamic Boarding School in Kampung Banjir Pasar Gunung Tua in fostering worship, Aqidah (belief), and morals within the community is commendable. Regarding worship, alumni serve as mosque imams, call for prayers (adzan), act as muezzins, teach Quranic recitation, and collect and distribute zakat. Alumni also instill and promote Aqidah values to prevent acts of polytheism. In terms of morals, alumni speak softly, dress modestly, and visit the sick. 2) The supporting factors for alumni in their roles include the harmonious relationship between Darussalam Islamic Boarding School alumni and the community, with the majority of the Partimbakoan population being Muslim. Meanwhile, the inhibiting factors include conflicting activities with other community events and the community's work schedules leading to a lack of interaction with alumni.